FEATURES INTRODUCTION OF A SINGLE CURRENCY IN THE COUNTRY'S INTEGRATION INTO AN ECONOMIC UNION - A. G. Kazakova (Модернизация, инновация, развитие, 2016)
The aspects of the introduction of the single currency calculations economic and geographic integration zone. Presented the basic theory of optimum currency areas. Made conclusions about the main advantages and disadvantages of the theory of optimal currency areas. We describe the world's major world currencies - the dollar and the euro. It makes projections about the prospects of other reserve currencies in the world. Presented diff erent approaches are proposed for the introduction of a single currency settlement currency and a single monetary zone in the territory of the Eurasian Economic Union.